Eficiencia de consorcios bacteriano – microalgal para la disminución de la concentración de materia orgánica en aguas residuales de la ESPAM MFL - Bermúdez Demera, Campos Xavier (2016)
This research was made with the objective of evaluating the relation between the consortium and the concentration of BOD5 in wastewater of the ESPAM MFL, developed with two factors under study: bacterial consortium (Sccharomyce cerevisiae, Bacillus acid lactic, Lactobacillus acidophilus) and micro algae consortium (Chorella, Desmodesmus). Six combinations were formulated with three levels of microbial consortium and two levels of micro algae consortium, getting the following treatments: T1 (270:270 µdm3), T2 (270:410 µdm3), T3 (410:270 µdm3), T4 (410:410 µdm3), T5 (540:270 µdm3), T6 (540:410 µdm3). The experimental unit was 0.27 dm3 of waste water sample from the wastewater treatment plant of the ESPAM MFL. Biological Oxygen Demand (BOD5), Dissolved Oxygen (DO) and Potential Hydrogen (pH). The following parameters were determined. Based on the results it is concluded that a mixture of consortia as bacterial (Sccharomyce cerevisiae acid lactic Bacillus acidophilus Lactobacillus) and micro algae (Chlorella, Desmodemus) favors the decrease of the concentration of organic matter in sewage, helping in bioremediation processes. The quality of the effluent from the WWTP presented inadmissible criteria with certain environmental regulations, situation improved significantly with the implementation of the proposed consortia. The efficiency of bacterial consortia - micro algae was 97.77%, showing a reduction of BOD5 45 times less than its initial value.